Modelos de avaliação de viabilidade, governança em megaprojetos e a aplicabilidade das metodologias 5CM e FEL em projetos de infraestrutura: o caso RNEST - Lidiane Pedra Vieira Melo (2023)
Large-scale projects always involve high costs, lengthy execution times, and considerable resources. By analyzing governance across different countries, we can identify ways to enhance project management in Brazil. This work contributes to the effective implementation of governance in infrastructure projects, suggesting improvements to assist in making more assertive decisions regarding the use of public resources, resulting in competitive advantages, investments, economic growth, sustainability, and job creation. Governance processes such as 5CM and FEL, focused on applying feasibility analysis methods considering technical, economic, and environmental aspects, are presented to support proposals for governance enhancement. Understanding the importance of rationalization in the decision-making process, the challenges faced, and the paths taken by countries to improve the management of public investments is essential for this discussion and suggestion of governance enhancement in the Brazilian context. The experience of the RNEST Project served as a lesson on the importance of studies in decision-making and how corruption and biases can interfere in this process. Interviews with those involved in the process revealed shared challenges and highlighted the need to reorganize governance and the gains achieved with the implementation of methodologies such as FEL and 5CM, which contribute to significant gains.